2019
DOI: 10.1177/2150132719882760
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a Prediction Rule for Metabolic Syndrome Risk Assessment Suitable for Developing Countries

Abstract: Background: Metabolic syndrome (MetS) is a cluster of cardiometabolic disturbances that increases the risk of cardiovascular diseases (CVD) and type 2 diabetes mellitus (DM). The early identification of high-risk individuals is the key for halting these conditions. The world is facing a growing epidemic MetS although the magnitude in Egypt is unknown. Objectives: To describe MetS and its determinants among apparently healthy individuals residing in urban and rural communities in Egypt and to establish a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 78 publications
0
18
2
Order By: Relevance
“…The literature search returned 7744 results after removing duplicates. We reviewed 362 full texts, of which 110 studies met inclusion criteria (28‐30, 33‐138). See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search returned 7744 results after removing duplicates. We reviewed 362 full texts, of which 110 studies met inclusion criteria (28‐30, 33‐138). See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, out of the 27 included papers, 25 report about the development of one or more risk model or score [19][20][21][22][23][24][25][26][27][28][29][30]32,33,[35][36][37][38][39][40][41][42][43][44][45], and 2 studies report about the development and validation of one or more risk model or scores on an external population [31,34]. Overall, the 27 studies reported 43 models, out of which 27 models were selected for full data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the observed incidence/prevalence of MetS at the end of the study is not reported in over fourty-one percent of the studies [19,20,26,32,36,37]. For those that reported it, the prevalence/ incidence of MetS ranged from as little as 7.9% [31] to as high as 57.8% [45]. In all the 17 risk scores targeting adults, various combinations of risk factors (predictors) were considered signi cant in the respective nal model.…”
Section: Mets Risk Models or Scores For Adultsmentioning
confidence: 99%
See 2 more Smart Citations